2010
DOI: 10.1007/s11671-010-9787-7
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale Synthesis of β-SiC Nanochains and Their Raman/Photoluminescence Properties

Abstract: Although the SiC/SiO2 nanochain heterojunction has been synthesized, the chained homogeneous nanostructure of SiC has not been reported before. Herein, the novel β-SiC nanochains are synthesized assisted by the AAO template. The characterized results demonstrate that the nanostructures are constructed by spheres of 25–30 nm and conjoint wires of 15–20 nm in diameters. Raman and photoluminescence measurements are used to explore the unique optical properties. A speed-alternating vapor–solid (SA-VS) growth mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…Figure 3(a) shows the TEM image of the resulting products synthesized at 1250 °C, which exhibit a single rod-like structure with a diameter of about 60 nm. It can be observed that the nanorod is just one-layer structure with smooth surface and homogeneous diameter which is different from the reported papers (Meng et al , 2011). The corresponding SAED pattern [bottom left insert; Figure 3(a)] of the nanorod exhibits a row of well-defined spots running parallel to the nanorod growth axis and other spots running nearly normal to the growth axis.…”
Section: Resultscontrasting
confidence: 93%
“…Figure 3(a) shows the TEM image of the resulting products synthesized at 1250 °C, which exhibit a single rod-like structure with a diameter of about 60 nm. It can be observed that the nanorod is just one-layer structure with smooth surface and homogeneous diameter which is different from the reported papers (Meng et al , 2011). The corresponding SAED pattern [bottom left insert; Figure 3(a)] of the nanorod exhibits a row of well-defined spots running parallel to the nanorod growth axis and other spots running nearly normal to the growth axis.…”
Section: Resultscontrasting
confidence: 93%
“…However, there are still some challenges for SiC nanomaterial’s photoluminescence (PL) characteristics. The PL characteristics are observed to be quite variable, which strongly depends on the morphology (SiO 2 ), size (diameter), structure (defects) 7 25 . Shena et al 20 synthesized the SiC/SiO 2 nanowires with emission peak at 408 nm, the SiC/SiO 2 nanowires synthesized by Zhang et al 17 shows emission peak at 438 nm and Shen et al synthesized the SiC/SiO 2 nanowires with emission peak at 401 nm 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the high-density SiC/SiO 2 core-shell nanowires were synthesized on the nickel coated SiO 2 (100 nm)/Si substrate by chemical vapor deposition (CVD) method at 1000 °C with ferrocene precursor. The CVD technology was used to control the shape and composition of the as-synthesized nanowires to improve PL properties which are not worse than the previous papers [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
mentioning
confidence: 99%
“…On the other hand, Meng et al . synthesized the chained homogeneous nanostructure by the anodic aluminum oxide template (AAO)‐assisted chemical vapor reaction process and proposed a speed alternating VS growth mechanism . Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Meng et al synthesized the chained homogeneous nanostructure by the anodic aluminum oxide template (AAO)-assisted chemical vapor reaction process and proposed a speed alternating VS growth mechanism. 13 Li et al reported a kind of necklace-like single crystalline b-SiC microwhiskers self-assembled through the carbothermal reduction process without any templates and catalysts. 14 Studies found that both the reported two nanochains heterostructures were grown as single crystalline SiC strings with periodic SiC beads and wrapped by the amorphous SiO 2 layer, which can be appointed type-II SiC nanochains.…”
Section: Introductionmentioning
confidence: 99%